New Allergens of Anise and Caraway - Słownianek, Marta; Leszczyńska, Joanna (Lodz University of Technology Press, 2015)
Spices are widely used in cuisine around the world to improve taste and smell values of many dishes and products and are a simple way to achieve good health due to the presence of certain compounds, active substances and even minerals that are needed for our body. Unfortunately they have some disadvantages, as part of their proteins have allergenic properties and contributes to the food hypersensitivity. Allergy to spices makes up approximately 1-4% of all food allergies [1]. Therefore undeclared by manufacturers presence of spices in many dishes and food products pose a threat to health of sensitized persons. The aim of research was identification of potentially allergenic proteins in anise and caraway.